The Relationship between Occupational Safety and Health (OHS) and the Work Effectiveness of Medical Records Officers at Dr. Hasan Sadikin General Hospital Bandung in 2026 - Wulandari, Revita; Elfi; Subianto, Totok; Abdurachman, Agus Setiawan (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Occupational Safety and Health (OSH) is an important aspect in creating a safe work environment and supporting work effectiveness, including for medical records officers who face various occupational risks. This study aimed to determine the relationship between OSH and the work effectiveness of medical records officers at Dr. Hasan Sadikin General Hospital, Bandung, in 2026. This investigation used a quantitative method with an analytic approach and a cross-sectional design. The sample consisted of 60 respondents selected utilizing total sampling considering inclusion and exclusion criteria. Data were collected utilizing questionnaires and analyzed utilizing the chi-square test. The outcomes revealed that most respondents had a good level of OSH (58.3%) and good work effectiveness (53.3%). However, statistical analysis indicated that there was no significant relationship between OSH and work effectiveness (p-value = 0.490 ≥ 0.05). This finding suggests that work effectiveness is not solely influenced by OSH implementation but also by other factors such as work experience, skills, and work systems. Nevertheless, OSH implementation remains important in creating a safe and comfortable work environment to support the optimal performance of medical records officers.